Extrusion-based 3D co-printing: Printing material design and novel workflow for fabricating patterned heterogeneous tissue structures. (March 2023) - Wang, Pengju; Sun, Yazhou; Li, Dekai; Ma, Ziyang; Zhang, Bohan; Diao, Liwei; Liu, Haitao
Graphical abstract: The feasibility of extrusion-based 3D co-printing is verified through mold-assisted structured ink preparation and process parameter optimization. To determine the design parameters including structured ink height and cross-section, both structured inks with material distribution of core–shell and symmetric cross-section, were extensively investigated by computational fluid dynamics simulation. Also, a novel workflow to the design and fabrication of structured printing materials for extrusion-based 3D co-printing is presented. We envisage this approach may enrich 3D printing while facilitating the fabrication of heterogeneous tissue structures. Highlights: A structured ink preparation method with controlled material distribution for heterogeneous structures is developed. The methodology to determine the design parameters of structured inks is presented. The material distribution in the cross-section of extruded fibers for heterogeneous structures is customized. The mode of 3D printing is expanded in a cost-effective and accessible pathway. Abstract: Extrusion-based 3D printing (E3DP) is commonly used both in in vitro and in situ biofabrication, due to the wide range of biomaterials and cells available and the low cost. However, it is challenging to fabricate such functional scaffolds due to limitations in ink performance, which must match the physicochemical and biological features of tissues. This study aims to bridge the gap via controlling the material distribution before printing. Here a new approach for preparing structured inks for E3DP is proposed. The feasibility is verified through ink preparation and process parameter optimization. These inks are fabricated by the integrated technology of casting and 3D printing. Computational fluid dynamics (CFD) simulation is employed to simulate the ink flow through the channels of printheads. The geometric parameters of these inks are determined by analyzing the cross section of the extruded fibers. Inks with core–shell cross section are investigated to clarify the effect mechanism of structured inks on printed fibers. Inks with symmetric cross section are exemplified to show the diverse printable structures. Finally, a novel workflow to the design and fabrication of structured printing materials for E3DP is presented. This approach may enrich E3DP while facilitating the fabrication of heterogeneous tissue structures.